The Urgency of the Existence of Islamic Banking (Comparative Study with Conventional Banking) - Muhammad Ali Adnan; Atika Sunarto (LEGAL BRIEF, 2021)
Banking has an important role in the development of a country's economy. Banking is a business entity that provides services in the payment traffic and circulation of money in the world. Islamic bank is a bank that conducts business activities based on Islamic principles, namely the rules of the agreement based on Islamic law between banks and other parties to finance business activities and / or deposit funds and other activities. The method used in this research is the normative method, namely legal research which is carried out by examining library materials or secondary data using a statutory approach, a conceptual approach and a comparative approach. The sources of data obtained are secondary data sources that come from literature studies by reviewing, analyzing and processing literature, laws and regulations, journals, articles, and writings related to Islamic banks and conventional banks. The results show that there is an urgency for the existence of Islamic and conventional banking in Indonesia in accordance with the interests of society.